(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article discusses low-level laser therapy (LLLT) as an effective therapeutic tool in the context of orchiectomies in dogs, focusing on its effects on reducing inflammation and providing analgesia. The research is based on the current concept of alternative and complementary therapies in veterinary medicine, which recognizes the potential of LLLT to improve postoperative recovery by promoting healing, pain control, and inflammation modulation. The main objective is to reflect on the benefits of LLLT applied in surgical procedures in dogs, with an emphasis on orchiectomies, and to discuss the most effective protocols for optimizing clinical outcomes. The methodology adopted is qualitative in nature, based on a literature review of academic studies, scientific articles, and recent clinical trials investigating the use of LLLT in veterinary medicine, specifically in minor surgeries. The results indicate that LLLT has been shown to be effective in reducing pain and inflammation, promoting faster and more comfortable recovery for animals. It was also observed that the combination of LLLT with traditional analgesics and other treatments can result in more effective management of postoperative pain. It is concluded that low-level laser therapy plays an important role in the recovery of dogs after orchiectomies, being essential to minimize the use of conventional medications and improve the quality of life of animals during the recovery process.